Religionsunterricht und Ideologiekritik: Zur Dekonstruktion von Verschwörungserzählungen - Krahn, Annika (Evangelische Theologie, 2024)
The author distinguishes conspiracy narratives from conspiracy myths or from a conspiracy ideology and decodes possible rhetorical devices of conspiracy narratives. These narratives assume that certain individuals or groups of people influence important events or crises in the world and thus deliberately harm the population, but at the same time keep them in the dark about their goals. Consequently, most conspiracy narratives are basically anti- Semitic, as Jews are usually marginalized in reality, but are portrayed as an allegedly powerful group in conspiracy narratives. This article aims to explain the extent to which religious education in public schools should address and deal with conspiracies and why it is important to do so. As a subject of conviction, religious education in particular is able to critically examine convictions and ideologies, i. e. as a conviction itself. Concrete points of contact with content areas from the core curriculum for secondary school in North Rhine-Westphalia close the consideration.